2019
DOI: 10.1136/gutjnl-2019-318374
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt consumption and risk of conventional and serrated precursors of colorectal cancer

Abstract: Contributors XiZ, YC and XuZ had full access to all the data in the study and took responsibility for the integrity of the data and the accuracy of the data analysis. Study concept and design: XiZ, YC, XuZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…The observed relationships were modest and limited to large or advanced adenomas. One recent report from two large US cohort studies found an inverse association only among men who consumed yogurt and risk of AP, but no associations were found for SP risk or for polyp risk among women (53) . Instead, we found a possible weak association with overall AP odds in the Biofilm Study and a significant association with AP odds among women and a strong association with HP in the TCPS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The observed relationships were modest and limited to large or advanced adenomas. One recent report from two large US cohort studies found an inverse association only among men who consumed yogurt and risk of AP, but no associations were found for SP risk or for polyp risk among women (53) . Instead, we found a possible weak association with overall AP odds in the Biofilm Study and a significant association with AP odds among women and a strong association with HP in the TCPS.…”
Section: Discussionmentioning
confidence: 94%
“…Instead, we found a possible weak association with overall AP odds in the Biofilm Study and a significant association with AP odds among women and a strong association with HP in the TCPS. The heterogeneity in the design of these studies may contribute to the differences including variation in exposure definition (several assessed broader categories including fermented dairy products) (38)(39)(40)(41)(42)(43) , extreme heterogeneity of available probiotics and yogurt products (including both the types and quantities of lactic acid-producing bacteria strains contained in each), the underlying population and diet and analytic methods including controlling for confounders (42,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) . Another possible explanation for the inconsistent findings may be misclassification of polyp status in many of the previous studies given the recent understanding of enhanced risk with SSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the recent work by Zheng et al published in the Gut journal titled ‘Yogurt consumption and risk of conventional and serrated precursors of colorectal cancer’ 1. This impressive result was widely reported and rapidly disseminated and attracted great public health attention.…”
mentioning
confidence: 94%
“…Supplementation of Lactobacillus casei has been reported to enhance anti-tumor immunity in colon cancer model by promoting potent Th1 immune responses, activity of CD8 + T and NK cells in ltration in the tumor tissue [11]. Moreover, several cohort studies indicated that probiotics such as Bi dobacterium and Lactobacillus produced from longterm dietary ber and yogurt contributed to cancer prevention and treatment [12,13].…”
Section: Introductionmentioning
confidence: 99%